ديدان الـGyrodactylus spp. المتطفلة على أسماك الكارب في مزرعة السن (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
تمت دراسة ديدان الـ Gyrodactylus spp. (G.) الطفيلية عند 440 سمكة كارب عادي بأعمار 40 يوما" وحتى سنتين، جرى الاعتيان عشوائياً بفاصل  15 يوما" من مزرعة السن خلال الفترة 4-10-2000 حتى 2-10-2001، تم تعيين النوعين G.medius وG.cyprini على الجلد والزعانف غالباً  وفي التجويف الفموي والحفرتين الأنفيتين ونادراً على الغلاصم. بلغ معدل الخمج (الإصابة) بديدان الـ(G.) %17.73 وكان النوع G.medius الأكثر انتشاراً بمعدل 17.5%، أبدت هذه الطفيليات علاقة بيئية مباشرة مع بعض المؤشرات البيئية خصوصاً الحرارة. سجل هذان النوعان لأول مرة في سوريا. A study was done on the parasitic gyrodactylus – worms of 440 Cyprinus carpio fish, age range from 40 days till tow years. Carp were captured every 15 days between October 2000 and October 2001 in the Al-Sinn farm. Gyrodactylus. Medius and G. cprini were identified mostly on the fins and skin, and in mouth and nasal cavity,But  rarely on gills. Gyrodactylus spp. infection rate is 17.73% of the hosts, where as G.medius more distributed in average 17.5%. (G.) had a clear seasonal especially occurrence in correlation with temperature. G.medius and G.Cyprini are recorded for the first time in Syria.